ANALISIS PENERAPAN MANAJEMEN LABA DALAM MENINGKATKAN KUALITAS PERUSAHAAN BERDASARKAN NILAI-NILAI ISLAM - Juwita Putri Wulandari; Chuzaimah Batubara (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
Earnings management is generally considered an unethical behavior, as it implies management discretion over accounting data, which may lead to manipulation of financial information available. However, companies' involvement in social responsibility projects shows that they care about the well-being of society, which goes beyond profits. The amount of profit generated. The amount of profit generated. Earnings management seems to have become a global corporate culture carried out by all companies. With the development of the corporate world, each entity must be able to compete with the products of companies in their respective sectors. Although in theory, performance management is considered halal when it does not conflict with Generally Accepted Accounting Principles (GAAP), the practice of performance management is considered incompatible with the values contained therein